The viral game: The global football community's response to epidemics and pandemics in the twenty-first century - Salkeld, P. (The Middle Ground Journal, 2020)
The twenty-first century has seen health crises related to SARS, Swine Flu, Ebola, Zika, and COVID-19. Nations cooperated with supranational groups when deciding what to do with football operations in these crises except during the COVID-19 pandemic when the "Ostrich Alliance" viewed it as interference with their sovereignty.